Improved Current Decoupling Method for Robustness Improvement of LCL-type STATCOM Based on Active Disturbance Rejection Control - Minglei Wang (IEEE Access, 2019)
When theoretically studying the control method of LCL-type static synchronous compensator (STATCOM), we often ignore the influence of complex power grid on the stability and reactive compensation performance of STATCOM. Improving traditional current decoupling method with PI controller (PI decoupling) in synchronous (dq) reference frame, an original current decoupling method with active disturbance rejection controller (ADRC decoupling) is proposed in this paper. First, the influence of internal and external disturbances on STATCOM with PI decoupling method is analyzed. External disturbances include harmonic grid voltage and grid inductance variation. Internal disturbances come from coupled channels between d axis and q axis, and parameter perturbations of LCL filter. Second, the principle of ADRC decoupling method applied to LCL-type STATCOM is analyzed in detail. Taking advantage of ADRC's capability to estimate and compensate for the “total disturbances”, robustness of STATCOM is improved. Comparing with PI decoupling method, ADRC decoupling method can improve the disturbances rejection performance and stability of LCL-type STATCOM. Finally, results from STATCOM simulation model show the effectiveness and superiority of this original method.